2022
DOI: 10.1038/s41598-022-07490-z
|View full text |Cite
|
Sign up to set email alerts
|

In hospital risk factors for acute kidney injury and its burden in patients with Sars-Cov-2 infection: a longitudinal multinational study

Abstract: Acute kidney injury (AKI) is associated with increased mortality in most critical settings. However, it is unclear whether its mild form (i.e. AKI stage 1) is associated with increased mortality also in non-critical settings. Here we conducted an international study in patients hospitalized with SARS-CoV-2 infection aiming 1. to estimate the incidence of AKI at each stage and its impact on mortality 2. to identify AKI risk factors at admission (susceptibility) and during hospitalization (exposures) and factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…The association between AKI and increased mortality in COVID-19 was evident in the earliest reports [ 50 ]. It is now widely accepted that even mild AKI (stage 1) confers increased risk of mortality and risk increases as the severity of AKI increases [ 11 ▪ , 20 ▪ , 44 ]. Cohort studies have shown an in-hospital mortality of around 40% of all patients with any AKI [ 11 ▪ , 44 ], which increases to 62% for patients with AKI in ICU [ 20 ▪ ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The association between AKI and increased mortality in COVID-19 was evident in the earliest reports [ 50 ]. It is now widely accepted that even mild AKI (stage 1) confers increased risk of mortality and risk increases as the severity of AKI increases [ 11 ▪ , 20 ▪ , 44 ]. Cohort studies have shown an in-hospital mortality of around 40% of all patients with any AKI [ 11 ▪ , 44 ], which increases to 62% for patients with AKI in ICU [ 20 ▪ ].…”
Section: Discussionmentioning
confidence: 99%
“…It is now widely accepted that even mild AKI (stage 1) confers increased risk of mortality and risk increases as the severity of AKI increases [ 11 ▪ , 20 ▪ , 44 ]. Cohort studies have shown an in-hospital mortality of around 40% of all patients with any AKI [ 11 ▪ , 44 ], which increases to 62% for patients with AKI in ICU [ 20 ▪ ]. The attributable mortality of AKI in COVID-19 is not well characterised and it remains unclear to what extent AKI is playing a causative role in risk for death or merely reflective of disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations